USING FACEBOOK AS A RESILIENCE STRATEGY BY FRENCH DEPARTMENT STUDENTS DURING THE PANDEMIC - Souad Benabbes (International Journal of Innovative Technologies in Social Science, 2024)
In recent years, Facebook has become a crucial tool for learning during the pandemic, serving as a platform for communication and collaboration between students and teachers. With the transition to distance learning, Facebook has helped maintain significant social and academic interactions. The social network has offered opportunities for collaborative and constructivist learning, where students can share resources, discuss concepts, and receive real-time educational support.This article explores how Facebook has played an essential role in the continuity of learning during the pandemic by facilitating dynamic and interactive learning environments. Through groups, pages, and online events, Facebook has allowed students from the French department of the University of Oum El Bouaghi to create virtual learning communities. These spaces provide crucial emotional and academic support for students facing isolation and uncertainty.